2018
DOI: 10.18006/2018.6(2).414.424
|View full text |Cite
|
Sign up to set email alerts
|

EXTRACTION AND CHARACTERIZATION OF CELLULOSE FROM JACKFRUIT (Artocarpus integer) PEEL

Abstract: In the present study, cellulose was extracted from de-pectinated peel of Jackfruit. The peel was treated with alkali followed by a chemical process treatment. In present study, yield of jackfruit cellulose was 27g / 100g. The average particle size and zeta potential value of extracted cellulose is 0.730nm and -15.7mV respectively. Further, morphological characterization was carried out by using scanning microscopy. FTIR spectroscopy analysis revealed the presence of major absorptions indicative of cellulose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Increasing stiffness and rigidity of the fibre owes to the better crystallinity of the fibre after treatment. Similar results were obtained by Sundarraj et al in year 2018 which confirmed the removal of amorphous material on fibre surface owing to the better crystallinity index and crystallinity percentage of the jackfruit peel [24].…”
Section: X-ray Diffraction Analysissupporting
confidence: 88%
“…Increasing stiffness and rigidity of the fibre owes to the better crystallinity of the fibre after treatment. Similar results were obtained by Sundarraj et al in year 2018 which confirmed the removal of amorphous material on fibre surface owing to the better crystallinity index and crystallinity percentage of the jackfruit peel [24].…”
Section: X-ray Diffraction Analysissupporting
confidence: 88%
“…With regard to the SC, which is the ability of a material to increase in bulk, WDF and ADF illustrate comparable values (6.17 and 6.79 ml/g, respectively). The SC of MDPF extracts is higher than that of the commercial DF of soybeans and cellulose (5.47 and 4.15 ml/g, respectively) (Chen et al, 2015; Sundarraj & Ranganathan, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Anwar, Bundjali, & Arcana, 2015). Raj and Ranganathan (2018) studied reported the cellulose extraction from the depectinated jackfruit peel by treating the peel with alkali and followed by a chemical process. After chemical modifications of the nanocellulose and its derivatives, they are used extensively because of their high aspect ratio of length to diameter and excellent mechanical strength (B.…”
Section: Cellulosementioning
confidence: 99%